Persepsi Pengguna Rokok Elektrik Laki-laki Usia 15 Tahun Keatas Terkait Penyakit Paru - Indriyawati, Dwi Titus; Martha, Evi (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2024)
E-cigarettes are used to reduce addiction to tobacco cigarettes and become a transition to get out of the habit of smoking tobacco. There has been an increase in smoking in the age group of adolescents, students, and college students. Qualitative research methods use primary data with data collection, namely in-depth interviews. Informants are e-cigarette users who are over 15 years old and have used e-cigarettes for at least 3 months. Data analysis used thematic analysis. The view of smoking behavior was that smoking was started because of the influence of friends and curiosity. There is influence from the social environment, family, and peers to smoke. Views and awareness in the use of electric cigarettes on health. Information about the dangers of electric cigarettes is obtained through the internet, cigarette packages, or information from friends. The severity of lung disease is felt such as coughing, shortness of breath, and fatigue when exercising. Barriers to quitting smoking are still feeling comfortable, cheap, easy access to buying, no one recommends quitting smoking, not knowing the negative effects of e-cigarettes. From this research, it was concluded that of the 6 selected informants who used e-cigarettes, the perception of the dangers of e-cigarettes on lung health was still low.